Adjunct liraglutide use in people with type 1 diabetes in the St Vincent's Healthcare Group, Dublin: An Irish perspective. (2019) - Harkin, Patricia; McKenna, Malachi; Canavan, Ronan; Crowley, Rachel; O'Shea, Donal
No abstract available